“Does the Response to Morning Medication Predict the ADL-Level of the Day in Parkinson’s Disease?” - Trine Hørmann Thomsen; Troels Wesenberg Kjær; Lene Bastrup Jørgensen; Anita Haahr; Kristian Winge (Parkinson's Disease)
Background. Individuals with Parkinson’s Disease (PD) have bradykinesia during mobility tasks in the morning before intake of dopaminergic treatment and have difficulties managing Activities of Daily Living (ADLs). Early morning off (EMO) refers to off-states in the morning where the severity of bradykinesia is increased and causes a decrease in mobility related to wearing off of effects of medication. Measurements from devices capable of continuously recording motor symptoms may provide insight into the patient’s response to medication and possible impact on ADLs. Objectives. To test whether poor or slow response to medication in the morning predicts the overall ADL-level and to assess the association between change in bradykinesia score (BKS) and the risk of having disabilities within three selected ADL-items. Methods. In this cross-sectional study, the sample consists of 34 patients with light to moderate PD. Data collection encompasses measurements from the Parkinson KinetiGraph, and the ADL-limitations are assessed by the Movement Disorder Society Unified Parkinson Disease Rating Scale (MDS-UPDRS) Part II. Results. The association between UPDRS- II and BKS from the algorithm was −0.082 (p<0.01), 95% CL:−0.113; −0.042). The individuals experienced disabilities in performing “Speech” (p=0.004) and “Doing hobbies” (p=0.038) when being slow or poor responders to dopaminergic therapy. The PD patients’ L-dopa equivalent dose seems to be a strong predictor of the ADL-level in the morning. Conclusion. Slow response to the medication dosages in the morning is correlated with disabilities in the overall ADL-level in PD. The combination of PD-drugs and precise, timely dosages must be considered in the improvement of the ADL-level in PD patients.